Red giant asteroseismic binaries in the Kepler field: identifying gravitationally bound systems - Espinoza-Rojas, Francisca; Themeßl, Nathalie; Hekker, Saskia (Astronomy and astrophysics, 2025)
Context. Systems in which two oscillating stars are observed in the same light curve, so-called asteroseismic binaries (ABs), arise from either chance alignments or gravitationally bound stars. In the latter case, the detection of ABs offers a novel way to find binary systems and enables the combined use of asteroseismology and orbital dynamics to determine precise stellar parameters for both stars. Such systems provide valuable opportunities to test stellar models and calibrate asteroseismic scaling relations. While population synthesis studies predict approximately 200 ABs in the Kepler long-cadence data, only a few have been detected to date. Aims. Our aim is threefold. We aim to (1) expand the sample of detected ABs in Kepler data, (2) estimate global asteroseismic parameters for both stars in each AB, and (3) assess whether these systems are gravitationally bound. Methods. We performed an asteroseismic analysis of 40 well-resolved ABs identified in the Kepler long-cadence data. We matched these solar-like oscillators with Gaia DR3 sources using spectroscopic estimates of their frequency of maximum oscillation power, νmax. To assess whether each pair is gravitationally bound, we checked their projected separation and parallax consistency, and compared the observed total orbital velocity differences derived from astrometry with theoretical predictions from Keplerian orbits. Results. Most ABs appear to be chance alignments. However, we detected two systems, KIC 6501237 and KIC 10094545, with orbital velocities, seismic masses, and evolutionary stages consistent with a wide binary configuration, i.e. they have binary probability of ∼50% and ∼25%, respectively. Furthermore, we found 11 ABs that are likely spatially unresolved binaries based on Gaia multiplicity indicators. Conclusions. Our findings suggest that most seismically resolved ABs in the Kepler field are not gravitationally bound, in contrast to earlier population synthesis predictions. Remarkably, the two wide binary candidates identified here represent promising benchmarks for asteroseismic calibration. Spectroscopic follow-up is necessary to confirm their binary nature.
Online verfügbar: 06. November 2025
Gesehen am 12.02.2026